Implementasi Corporate Social Responsibility (CSR) dan Akuntansi Hijau dalam Meningkatkan Profitabilitas Perusahaan Pertambangan (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze how the implementation of Corporate Social Responsibility (CSR) and green accounting can contribute to enhancing the profitability of mining companies. A systematic literature review approach is employed, drawing from scholarly journals, books, and accredited reports that examine the relationship between CSR, green accounting, and profitability. The analysis reveals that CSR improves company reputation and stakeholder trust, while green accounting fosters cost efficiency and transparency in environmental management. Another key finding shows that integrating both approaches can reinforce corporate legitimacy and establish competitive advantages that support long-term profitability. The implications of this research highlight the need for sustainability strategies to be embedded within reporting systems and corporate policies so that mining companies can excel not only economically, but also demonstrate social and environmental responsibility.